2022
DOI: 10.3389/fgeed.2022.863193
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Genome Editing Technologies Towards Improved Nutrition, Environmental Sustainability and Poverty Reduction

Abstract: The Sustainable Development Goals (SDGs) were launched in 2015, with the top three goals being poverty eradication, improved food security and increased human health. All 17 SDGs have a target achievement date of 2030. These are ambitious and inspirational goals that require substantial innovation and technology adoption for successful achievement. Innovations in plant breeding have substantially contributed to transforming the efficiency of food production since the mid 20th century, with innovations emerging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…These results are in line with McFadden and Smyth (2019) who reported the majority of Canadians believe modern plant breeding will increase production as well as lead to a loss of biodiversity. For a review of the benefits of genome editing technologies, ( Smyth, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with McFadden and Smyth (2019) who reported the majority of Canadians believe modern plant breeding will increase production as well as lead to a loss of biodiversity. For a review of the benefits of genome editing technologies, ( Smyth, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, studies with field trials have revealed very promising results for GE to increase grain yield, a trait which has not been targeted on a large scale through transgenesis. Biotic and abiotic stress resistance, increased uptake of nutrient compounds, and reduced toxic compounds are targets of the GE approach and, together with increased yield, have the advantage of a reduced degree of regulatory oversight [ 96 , 155 , 156 ].…”
Section: Transgenic Versus Ge Plants: What Possible Future?mentioning
confidence: 99%
“…Advances in biology, ICT and engineering are repositioning the role played by biological resources and improving our ability to understand and take full advantage of the opportunities offered. In recent decades, biology advances have accelerated with new research tools such as CRISPR-Cas9, building on new knowledge of plant, animal and microbial genomes as well as big data [14,15]. Knowledge increases are used to increase the efficiency of crops, animals, biofuel, bioplastics and bioenergy production.…”
Section: Advantages Of Disruptive Scientific and Technological Develo...mentioning
confidence: 99%